Sensory Profile And Panelist Acceptance Level of Tomato (Solanum Lycopersicum L.) Juice Jelly Candy With The Addition of Various Flavored Yogurt - Delva Yugita; Yenni Okfrianti; Kamsiah Kamsiah (UNIVED Press, Dehasen University Bengkulu, 2026)
Purpose : This study aimed to analyze the effect of adding yogurt in six flavor variants—stroberi, lychee, grape, blueberry, mango, and plain—on the sensory profile and panelist acceptability of tomato juice jelly candy. Methodology: This experimental study used a completely randomized design with one factor, namely yogurt flavor variation, consisting of six formulations (F1–F6). The quantities of tomato juice, yogurt, gelatin, granulated sugar, and liquid sugar were kept constant across all formulations; the only difference among treatments was the yogurt flavor used. Sixty panelists participated in a triangle test for sensory sensitivity screening. A total of 42 panelists who passed the screening proceeded to descriptive scoring and hedonic testing for color, aroma, texture, and taste. Data were analyzed using a binomial test for panelist screening, the Kruskal–Wallis test for comparison among formulations, and pairwise post hoc tests when significant differences were detected. Results: A total of 42 of 60 panelists (70.0%) passed the sensory sensitivity screening. Yogurt flavor variation significantly affected the descriptive sensory scores of color, aroma, and taste, but did not significantly affect texture. In the hedonic test, significant differences were also observed for color, aroma, and taste, while texture did not differ significantly. Exploratorily, F1 (stroberi yogurt) showed the highest overall hedonic mean. Findings: These findings can serve as a basis for further research, since this study focused only on sensory variables. Future studies may examine nutritional content, bioactive compounds, and lactic acid bacteria content. Novelty: This study integrates sensory sensitivity screening, descriptive profiling, and hedonic testing to evaluate tomato juice jelly candy with flavored yogurt variants. Originality: Research on the addition of yogurt to fruit juice jelly candy has not been previously conducted. Conclusion: The addition of yogurt in different flavor variants affected both the sensory profile and panelist acceptability of tomato juice jelly candy. F1 is recommended as the overall best formulation based on the highest combined hedonic mean, although for some attributes it was not always significantly different from other formulations within the same significance group. Type of Paper : Research article.